ENT300 Jazaj’ Perfection Self-Service Laundry / Jedidiah Uti Christopher... [et.al] - Christopher, Jedidiah Uti; Eddie, Amy Mardiana; Apendi, Mohd Zulqarnain; Salihin, Siti Aisyah; Luta, Naretta Janne (2015)
Jazaj’ Perfection Self-Service Laundry is about twenty-hour’s self-service laundry. Our business located at Desa Ilmu Fasa 25, Taman Desa Ilmu, 94500 Kota Samarahan, Kuching, Sarawak. While there are many laundry service, Jazaj’ Perfection will excel due to its attention to detail regarding our users. Through unheralded users’ attention, Jazaj’ Perfection will slowly but surely gain market share as it provide self-service laundry to the entire people live in Kota Samarahan area. Moreover, we are believed that we will successfully compete with our competitors in a few years ahead. This is because the location we choose to operate our business is near to the resident area and higher institutions. They will need to use laundry service as our company has quick service to done laundry. We, Jazaj’ Perfection Self-Service Laundry, saw the opportunity that this business has the potential of success provided that it is handled efficiently. People will need our service when they are having a hectic life and busy.